Effect of planting dates on growth, flowering and multiplication of gladiolus (Gladiolus grandiflorus) cv. 'Solan Mangla' (Current Horticulture, 2024)
The experiment was conducted to find out the effect of planting dates on growth, flowering and multiplication of gladiolus (Gladiolus grandiflorus Andrews) cv. Solan Mangla at experimental farm of Department of Floriculture and Landscape Architecture, Dr Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan, during 2015- 16. The experiment was laid out in a randomized block design, comprising twelve planting dates starting from 13 February to 28 July 2015 at 15 days intervals. Among all the planting dates, earliest sprouting, slipping, bud break and flowering were observed for 28 July planting. Whereas, 13 February gave 100% sprouting, maximum number of florets (15.06), size of corms (3.99 cm), number of cormels/plant (97.40), weight of corms/plant (24.64 g) weight of cormels/plant (24.78 g) and 28 February planting were found to be at par with 13 February planting for all these parameters as well. Other than that, 28 February planting also recorded highest number of spikes (2.50), vase-life (7 days) and duration of flowering (39.33 days). However, maximum size of floret (10.33 cm) and heaviest spikes (89.03 g) were recorded for 30 March planting. This planting was also in accordance with 13 February and 14 April plantings for maximum number of florets (14.13) and spike length (93.54 cm). Hence, 13 February, 28 February and 30 March plantings were found to be the best for flower spike production. Moreover, 13 February also recorded best results for corms and cormel production in equivalence with 28 February planting for most of the corm and cormel parameters. However for marketable spikes, it is advisable to conduct staggered planting from during February-April.
Keywords: Flowering; Corm; Planting dates; Growth; Multiplication; Slipping; Bud break